Multifractal characteristics of soil particle size distribution of abandoned homestead reclamation under different forest management modes - Tingting Meng; Jichang Han; Yang Zhang; Yingying Sun; Zhe Liu; Ruiqing Zhang (Scientific Reports, 2024)
Abstract In this study, fast-growing poplar reclaimed from abandoned homestead in Xixian New District, Xi’an City, Shaanxi Province, was used as the research object to explore the multi-fractal characteristics of soil particle size distribution under different management modes of abandoned land (control), irrigation, fertilizer irrigation and mixed fertilizer irrigation. The results showed that the mean values of soil clay, silt and sand in abandoned land were 14.58%, 81.21% and 4.22% respectively, 14.08%, 79.92% and 5.99% under irrigation, 15.17%, 81.19% and 3.64% under fertilizer irrigation, and 16.75%, 80.20% and 3.05% in mixed fertilizer treatment. From 40 cm, with increasing soil depth, soil clay particles increase under irrigation, fertilizer irrigation, and mixed fertilizer irrigation modes. The single fractal dimension of soil particle size distribution (D) in each treatment ranges from 2.721 to 2.808. At 60–100 cm, D shows fertilizer irrigation > mixed fertilizer irrigation > irrigation > abandoned land, indicating that fertilization and irrigation can increase the fine-grained matter of deep soil particles and reduce soil roughness. Compared with abandoned land, under irrigation, fertilizer irrigation and mixed fertilizer modes the capacity dimension (D 0 ), entropy dimension (D 1 ), correlation dimension(D 2 ), shape characteristics of the multifractal spectrum (Δf) and overall inhomogeneity of the soil particle size distribution (D 0 –D 10 ) indicate an uneven distribution of soil particle size; fractal structure characteristics of soil (D −10 –D 0 ) indicate a simplified soil structure, and degree of dispersion of soil particle size distribution (D 1 /D 0 ) indicates that soil particle size is distributed in dense areas. Pearson correlation analysis showed that D was significantly correlated with clay, sand, D 0 –D 10 , soil organic matter (SOM) and soil available phosphorus (SAP) (P < 0.05). Stepwise regression analysis showed that clay was the main controlling factor of D and D 0 –D 10 changes. The research results can provide some potential indicators for the quality evaluation of abandoned homestead reclamation.